Selenium Donors at the Junction of Inflammatory Diseases - Alhasan, Rama; Kharma, Ammar; Leroy, Pierre; Jacob, Claus; Gaucher, Caroline (Current Pharmaceutical Design, 2019)
Selenium is an essential non-metal trace element, and the imbalance in the bioavailability of selenium is associated with many diseases ranking from acute respiratory distress syndrome, myocardial infarction and renal failure (Se overloading) to diseases associated with chronic inflammation like inflammatory bowel diseases, rheumatoid arthritis, and atherosclerosis (Se unload). The only source of selenium is the diet (animal and cereal sources) and its intestinal absorption is limiting for selenocysteine and selenomethionine synthesis and incorporation in selenoproteins. In this review, after establishing the link between selenium and inflammatory diseases, we envisaged the potential of selenium nanoparticles and organic selenocompounds to compensate the deficit of selenium intake from the diet. With high selenium loading, nanoparticles offer a low dosage to restore selenium bioavailability whereas organic selenocompounds can play a role in the modulation of their antioxidant or antiinflammatory activities.
Keywords: organoselenium